A cutting mechanism map for machining metallic sheets using electric current pulses. (8th June 2020) - Tan, Peiyu; Kumar, Praveen; Dutta, Indranath
Abstract: We describe a tool-less and free-form manufacturing process for cutting metallic sheets by extending an initial cut by passing a series of electric current pulses. As the electric current reverses its direction across a sharp cut, an electromagnetic force is generated that tries to open the initial cut. The reversal of electric current around the cut also results in current crowding at the cut-tip, thereby concentrating Joule heating in the vicinity of the cut-tip. The self-induced electromagnetic force works in tandem with the concentrated Joule heating at the cut-tip, resulting in extension of the initial cut by a finite amount upon passing an electric pulse. The cut grows parallel to the initial orientation via one of the three mechanisms, namely sharp crack extension, blow-hole formation and formation of elongated hole with buckled edges, depending on the current density and the temperature. A detailed cutting mechanism map has been developed that can be used for selecting proper parameters for electro-pulse induced cutting for obtaining desired cut profile. This work paves path for realization of a unique methodology for machining hard-to-cut conducting materials.